Serological detection of Chlamydophila psittaci in psittacids in captivity of the Biobío Region, Chile - Pinto, Karla (2018)
The parrots (Birds: Psitacidae), besides being one of the pets of greater increase in Chile in recent years, are important reservoirs of pathogens, including the zoonotic bacterium Chlamydophila psittaci. The objective of the study was to detect the presence of serum antibodies against C. psittaci in 30 parrots from three private breeding sites in the Biobío Region, through the detection of IgG antibodies by a commercial ELSA kit (ELISA InmunoComb®). Three adult parrots (3/24) were seropositive (10% prevalence) and none of the juveniles (0/6). The positive psitacids corresponded to an austral parakeet (Enicognathus ferrugineus), a slender-billed parakeet (Enicognathus leptorhynchus) and an Amazon parrot (Amazonas pretrei), all from the same hatchery. The first two species are native species of Chile.